A conceptual framework of tourism social entrepreneurship for sustainable community development. (December 2018) - Aquino, Richard S.; Lück, Michael; Schänzel, Heike A.
Abstract: The continuous search for responsible and sustainable practices in the tourism industry paves the way for alternative approaches to tourism development. Often, local communities are at the foreground of these innovative tourism entrepreneurship and development strategies. The emergence of social enterprises operating in tourism refocuses the agenda of engaging and developing disadvantaged and underdeveloped communities sustainably through the industry. Tourism social entrepreneurship (TSE) is suggested as a market-based strategy to address social problems whilst maximising the benefits and minimising the negative consequences that tourism may provide to host communities. To date, there is limited understanding of how TSE can be a catalyst for sustainable community development. The purpose of this paper is to address this gap in knowledge by conceptualising TSE as a more holistic strategy for sustainable community development. By critically analysing the literature, this paper situates TSE within and for community development. A conceptual framework that incorporates community development concepts, generic social entrepreneurship and TSE principles, and community capitals perspectives, is proposed. This conceptual paper contributes to the emerging literature on TSE and may assist the actors in the TSE system as they establish new community-centric social enterprises.